(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
Many small reservoirs in Northern Côte d’Ivoire are used for crop irrigation, livestock rearing or fishing. They generate moderated ichthyological catches for local populations. Thus, strategies for their sustainable exploitation should be put in place. This study was conducted to provide the first data on fishing activity on the Lavononkaha Dam Lake. From June 2020 to July 2021, field studies were undertaken with the objectives of characterising fishing gears used, studying catch composition, and evaluating exploitation parameters of the Oreochromis niloticus stock. Results obtained stated the practice of recreational fishing by 41 anglers. These fishermen used a total of 380 fishing lines, 92.11% of which were single fishing rod. Ten fish species were identified in catches with a particular abundance of Oreochromis niloticus (48.33%). In the fishery, this species has a longevity tmax of 3.7 years and grows towards asymptotic length L∞=24.68 cm at a growth rate K=0.810/year. Despite the high number of fishing gears used, the stock of the species is underexploited (E=0.34) and half of the specimens are caught after reaching sexual maturity. Thus, the possibilities of increasing fishing effort to increase yields of this species exist within certain limits to be specified. Vol. 9, No. 2, August 2022: 229-238